Comparative Legal Analysis of The Death Penalty Provisions In Indonesia: The State Of Pancasila Law's Perspective (Case Study of Law Numbers 1 Of 1946 And Law Number 1 of 2023 Concerning The Criminal Code) - Kurniawan, Kurniawan; Kantikha, I Made; Markoni, Markoni; Nardiman, Nardiman (Ann Publisher, 2024)
The death penalty is one tool used by law enforcement to deal with significant crimes. Its purpose is to deter criminals from committing similar crimes in the future and to make those who have not engaged them feel fearful of doing so. Following the reforms, the Republic of Indonesia's legal politics evolved into one that supports democracy. The surface issues concern how the death sentence laws are seen from the standpoint of the Pancasila legal state. This study aims to compare regulatory policies regarding the death penalty from the perspective of Pancasila's legal system. Normative juridical research is the analytical tool employed to explore this issue. The findings of this study, specifically the death penalty clauses included in Law Number 1 of 1946 and Law Number 1 of 2023 governing the Criminal Code, contain many different things that were initially the basic criminal death penalty, which were changed to special criminal penalties. There are also several relationships and comparisons between certain crimes because the principle of legality is still in effect. In the Indonesian context, the view of life is Pancasila, a joint agreement or consensus between the majority of the Indonesian nation.